Mining Mobility Patterns from Geotagged Photos Through Semantic Trajectory Clustering. Issue 4 (19th May 2018) - Cai, Guochen; Lee, Kyungmi; Lee, Ickjai
ABSTRACT: Increasing geotagged social media data has become a potential repository used to find common trajectory patterns. Various spatial trajectory behaviors have been studied in previous work. In this paper, we extract common trajectory patterns on semantic level. We enrich trajectories with additional contextual semantic annotations and propose a density-based method to find semantic common trajectory patterns with a novel similarity measure method. Real geotagged photo data are used in our experiments. Experimental results demonstrate that our methods are able to generate semantic common trajectory patterns.